Microbubble resonators for photoacoustic and photothermal characterisation of nanoparticles suspensions - Frigenti Gabriele; Cavigli Lucia; Ratto Fulvio; Centi Sonia; García-Fernández Tupak; Farnesi Daniele; Pelli Stefano; Nunzi Conti Gualtiero; Soria Silvia (EPJ Web of Conferences, 2024)
We discuss the implementation of Whispering Gallery Modes Microbubble resonators (MBRs) as unique platforms for photoacoustic (PA) detection and photothermal (PT) spectroscopy. In a first experiment, the MBR transducer allowed to detect the PA signal generated by a suspension of gold nanorods (GNRs) within its core, leveraging on the MBR sharp optical spectrum and high sensitivity towards mechanical perturbations. Both static and flow-cytometry configuration were tested, finding that the MBR mechanical modes help detection by decoupling the environmental noise from the PA oscillation. In a second experiment, the MBR transducer allowed to reconstruct the GNRs absorption spectrum through the photothermal (PT) conversion, leveraging on high sensitivity towards temperature variations. We verified the scattering-free nature of the detection by using milk-stained GNRs suspension. We also found that the active locking of the MBR resonance increases the system sensitivity by an order-of-magnitude. These results make MBRs interesting candidates for combined PA and PT characterisation of extremely small samples for medical diagnosis, quality controls in food safety and chemical production processes.